Diamonds are forever [videorecording (Blu-Ray)] - Barry, John, 1933-2011 (Metro-Goldwyn-Mayer Studios : Distributed by Twentieth Century Fox Home Entertainment, 2012)
"A fortune in stolen diamonds thrusts James Bond into action ... and [he] teams up with Tiffany Case ... to prevent his nemesis Blofeld ... from using the diamonds in a deadly laser satellite"--Container.